A study on knowledge regarding first aid among undergraduate medical students - Gore, Chaitali A.; Sankar, Sruthi; Sheriff, Shabnam; Anand, Swetha; L., Smrithika; Maiya, Swathi (International Journal Of Community Medicine And Public Health, 2017)
Background: Life is characterized by precarious twists and turns and risky conditions that emerge all the time. First aid is the immediate action taken to save a life and reduce the effects of injury and illness until medical help is obtained. This study aims at assessing the knowledge regarding first aid among undergraduate medical students and comparing the knowledge among different terms. Methods: A cross-sectional study was done among 150 undergraduate medical students of Vydehi Medical College, Bangalore. A questionnaire with 15 questions regarding the awareness and skills involved in first aid were used to assess the levels of awareness among undergraduate medical students. Data was entered in Microsoft Excel Sheet. Analysis was done using Statistical Package for Social Sciences version 21. Data was analysed using percentages and Chi-square test. Results: A total of 150 medical students filled the questionnaire, 50 each from 5th (2nd year), 7th (3rd year) and 9th terms (4th year). The overall scores were, 43 out of 150 students had excellent knowledge, 71 out of 150 needed improvement, 35 out of 150 had adequate knowledge and only 1 out of 150 had poor knowledge about First-Aid. The association between terms and level of knowledge was found to be statistically significant. Conclusions: First Aid knowledge among medical students needs improvement. Level of knowledge improved with increasing term but this was not sufficient and more training should be given to all medical students on first aid and basic life support.